Women and rural development - Trivedi, Tanuja (New Delhi : Jnanada Prakashan : Assisted by Text Book Promotion Society of India, 2009)
In Indian context.
Includes bibliographical references (p. [294]-299) and index.
Keywords: Women in rural development -- India; Rural women -- Political activity -- India; Rural women -- Employment -- India